Improving Teenagers' Self-Capacity Towards Zero Stunting Through The Implementation Of The "Si-Telur Petis" Application As A Screening For Non-Communicable Diseases In Selopamioro Village: Peningkatan Kapasitas Diri Remaja Menuju Zero Stunting Melalui Implementasi Aplikasi “Si-Telur Petis” Sebagai Skrining Penyakit Tidak Menular di Kelurahan Selopamioro - Rianita Elfrida Sinaga, Mei; Widi Istianti, Daning; Betaliani Wirata, Resta (Jukeshum: Jurnal Pengabdian Masyarakat, 2025)
The demands of learning tasks for today's teenagers spend a lot of time on activities using gadgets while less physical activity, and less healthy eating patterns. This condition is one of the causes of the high incidence of anemia, hypertension and diabetes mellitus in adolescence. The purpose of this community service is to realize healthy adolescents by increasing the capacity of adolescents both knowledge and skills in the Prevention of non-communicable diseases using the application “Si-Telur Petis”. The method of dedication is carried out by training on the use of the ‘Si-Telur Petis” application, screening for non-communicable diseases, namely anemia, hypertension and diabetes mellitus, mentoring of adolescent cadres for home visits. It was found that the activities carried out increased knowledge by 88% in adolescents regarding the Prevention of non-communicable diseases, improved skills of adolescent cadres in screening 70%, understanding of adolescent cadres in using and accessing the application “Si-Telur Petis” 100%, confident adolescent cadres make home visits. The continuity of the implementation of Posyandu remaja needs support and assistance from the local health center. Increasing the self-capacity of adolescents is the key in preventing non-communicable diseases so that superior generations are realized.